Stent-retriever alone versus combined use of stent-retriever and contact aspiration technique for middle cerebral artery M2 occlusions: a propensity score analysis. (8th November 2021) - Pérez-García, Carlos; Rosati, Santiago; Gómez-Escalonilla, Carlos; Arrazola, Juan; López-Frías, Alfonso; González, Eva; Fondevila, Jon; Vega, Pedro; Murias, Eduardo; Jimenez-Gomez, Elvira; Bravo Rey, Isabel; Macho, Juan; et al.
Abstract : Background: The optimal endovascular treatment (EVT) technique for middle cerebral artery (MCA) M2 segment occlusions remains unknown. We aim to analyze whether reperfusion rate, procedure times, procedure-related complications, and clinical outcome differed between patients with isolated M2 occlusions who underwent stent-retriever (SR) alone versus combined SR and contact aspiration (CA) as a front-line EVT. Methods: Patients who underwent EVT for isolated MCA-M2 occlusion were recruited from the prospectively ongoing ROSSETTI registry. Patients were divided regarding the EVT approach into SR alone versus SR+CA and propensity score matching was used to achieve baseline balance. Demographic, procedural, safety, and clinical outcomes were compared between groups. Multivariable logistic regression analysis was performed to identify independent predictors of first-pass effect (FPE) and 90-day modified Rankin scale (mRS) 0–2. Results: 214 patients underwent EVT for M2 occlusion, 125 treated with SR alone and 89 with SR+CA. Propensity score matchnig analysis selected 134 matched patients. The rates of FPE (42% vs 40%, p=1.000) and 90-day mRS 0–2 (60% vs 51%, p=0.281) were comparable between groups. Patients treated with SR alone had lower need of rescue therapy (p=0.006), faster times to reperfusion (p<0.001), and lower procedure-related complications (p=0.031). Higher initial Alberta Stroke Program Early CT Score was an independent predictor of FPE. Age, baseline National Institutes of Health Stroke Scale score, and procedure duration were significant predictors of good clinical outcome at 3 months. Conclusions: As front-line modality in M2 occlusions, the SR alone approach results in similar rates of reperfusion and good clinical outcomes to combined SR+CA and might be advantageous due to faster reperfusion times and fewer adverse events.